Adherence to the Dutch dietary guidelines is inversely associated with 20-year mortality in a large prospective cohort study - van Lee, L; Geelen, A; Kiefte-de Jong, J C; Witteman, J C M; Hofman, A; Vonk, N; Jankovic, N; Hooft van Huysduynen, E J C; de Vries, J H M; van 't Veer, P; Franco, O H; Feskens, E J M (European Journal of Clinical Nutrition)

The crucial first year: The development of students' motivation at a Business School-a Mixed Methods Study - Brahm, Taiga; Jenert, Tobias
The transition from school to university can be overwhelming for some students. While students' motivation is considered a strong predictor of performance, the development of motivation during students' transition from high school to university has rarely been investigated. Additionally, little is known about the relation of motivational aspects with other influences on study performance. The present mixed methods study addresses this research gap and examines the development of economics students' study motivation. The longitudinal mixed-method study included three waves of data collected using quantitative surveys and a series of five interviews conducted with 14 first-year students over eight months. Regarding students' development over time, the quantitative analysis showed a gradual decline in students' motivation. However, in the interviews, certain events during the first year were identified as critical incidents demotivating students. These insights into the development of students' motivation at a business school show that concrete incidents influence students' motivational development; thus, they could be transformed by structural changes.
Keywords: motivation; business school; higher education; latent growth curve model; longitudinal study; mixed methods; interview; students

Transition within higher education institutions (HEI): Differences in learning culture (LC) between first-year, bachelor, and master students at a business school - Gebhardt, Anja; Jenert, Tobias
Tertiary education comprises at least two phases, undergraduate and graduate studies. Often, the first year is regarded another, crucial phase where students familiarize with the study environment. It can be hypothesized that students' individual perceptions of learning and studying as well as the pedagogies they experience differ depending on their current study phase. Yet, differences between the phases in HE have rarely been investigated. To capture differences in student experiences in HE comprehensively, Jenert and Gebhardt (2010) have developed a framework describing Learning Culture in HEI. LC comprises a number of constructs on the three levels of the individual student, pedagogical interactions and the organization. The study first aims to quantitatively describe differences in LC between the phases of HE within a university. Based on this analysis, a second goal is to develop a deeper understanding of how students manage the transitions between different phases by applying qualitative research methods.
Keywords: Higher Education; Transitions; Bachelor; Master

A MINLP Approach for Planning the Renewal of Pipes in Drinking Water Networks - Stapel, Florian; Suhl, Leena
This article presents a novel Mixed Integer Nonlinear Programming (MINLP) approach for ﬁnding a renewal plan of pipes in a water distribution system. We formulate a MINLP model for ﬁnding the times of renewal and suited measurements of pipe dimensions in a multi-year planning horizon. The model includes a multi-period hydraulic simulation of the distribution systems behaviour thereby respecting the friction caused headloss as a nonlinear constraint. We apply the MINLP solver Bonmin to a test network and present ﬁrst numerical results. The models embedding into a general solution framework for water network problems consisting of network reduction and simulation steps in an interated way, is beign discussed. This latter discussion corresponds well to the recent results by C. Hallmann for the problem of tank planning within the mentioned solution framework that has been presented there for the ﬁrst time.

Self-determination and interest development of first-year mathematics students - Liebendörfer, Michael (Oberwolfach Reports)

Risk Reduction in Natural Disaster Management Through Information Systems: A Literature review and an IS design science research agenda - Schryen, Guido; Wex, Felix (International Journal of Information Systems for Crisis Response and Management (IJISCRAM))
Natural disasters, including earthquakes, Tsunamis, floods, hurricanes, and volcanic eruptions, have caused tremendous harm and continue to threaten millions of humans and various infrastructure capabilities each year. In their efforts to take countermeasures against the threats posed by future natural disasters, the United Nations formulated the ?Hyogo Framework for Action?, which aims at assessing and reducing risk. This framework and a global review of disaster reduction initiatives of the United Nations acknowledge the need for information systems research contributions in addressing major challenges of natural disaster management. In this paper, we provide a review of the literature with regard to how information systems research has addressed risk assessment and reduction in natural disaster management. Based on the review we identify research gaps that are centered around the need for acquiring general knowledge on how to design IS artifacts for risk assessment and reduction. In order to close these gaps in further research, we develop a research agenda that follows the IS design science paradigm.
Keywords: Natural Disaster Management; Risk Reduction; Hyogo Framework; IS Design Science; Literature review

Carbohydrate quality is not associated with liver enzyme activity and plasma TAG and HDL concentrations over 5 years in an older population - Goletzke, Janina; Buyken, Anette; Gopinath, Bamini; Rochtchina, Elena; Barclay, Alan W.; Cheng, Guo; Brand-Miller, Jennie C.; Mitchell, Paul (British Journal of Nutrition)
Non-alcoholic fatty liver disease (NAFLD) is closely associated with insulin resistance and obesity. Hence, carbohydrate quality could be of relevance to the risk of NAFLD, but prospective data are lacking. The aim of the present study was to investigate longitudinal associations between carbohydrate quality (including dietary glycaemic index (GI) and intakes of sugar, starch and fibre) and markers of liver function in an older Australian population. The analysis was based on 866 participants ( ≥ 49 years) of the Blue Mountains Eye Study with fasting blood specimens and dietary intake data at baseline and 5-year follow-up. Multi-level mixed regression analysis was used to relate dietary GI and sugar, starch and fibre intake to the liver enzymes alanine aminotransferase (ALT) and γ-glutamyltransferase (GGT), as well as fasting TAG and HDL-cholesterol (HDL-C). After adjustment for potential confounding factors, a lower fibre intake was cross-sectionally related to higher GGT ( P = 0·02) and fasting TAG ( P = 0·002) levels, with fruit fibre being the most relevant fibre source ( P = 0·095 for GGT; P = 0·003 for TAG). A higher dietary GI was associated with lower HDL-C ( P = 0·046). Changes in carbohydrate quality during 5 years were not related to changes in ALT, GGT, TAG or HDL-C ( P ≥ 0·08). In conclusion, the absence of longitudinal associations between carbohydrate quality and liver enzymes and serum lipids in this older population does not support a major role of carbohydrate nutrition in liver function among the elderly.

Time trends in dietary fat intake in a sample of German children and adolescents between 2000 and 2010: not quantity, but quality is the issue - Libuda, Lars; Alexy, Ute; Kersting, Mathilde (British Journal of Nutrition)
Dietary fat intake in childhood may influence the risk for developing chronic diseases. The objective of the present study was to examine secular trends in the parameters of fat intake between 2000 and 2010 in a sample of German children and adolescents ( n 808) participating in the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) Study. Dietary data from 4380 3 d weighed dietary records were analysed using repeated-measures regression to determine time trends in fat quantity, i.e. the intake of total fat, and in fat quality, i.e. the ratios of SFA, MUFA and PUFA. In young children (2–3 years) and in adolescents (13–18 years), total fat intake remained stable over time, but decreased by 0·08 % of total energy (%E) per year in 4–12-year-old children. In 2010, median fat intake was at the upper end of the recommendations. SFA intake decreased slightly in 2–3- and 4–12-year-old children by 0·09 and 0·05 %E per year, respectively. MUFA and PUFA intakes remained stable in all the age groups except in adolescents. Here, PUFA intake decreased initially, but increased between 2005 and 2010. In 2010, only between 3 and 18 % of the respective age groups had an intake of SFA or PUFA within the recommendations. In conclusion, fat quantity and quality did not change substantially between 2000 and 2010. Fat quality, in particular, needs to be improved, since a large percentage of our sample did not meet the recommended intakes for SFA and PUFA.

How Business Students Attitudes towards their University and Studying Develop during the First Year: A Qualitative Longitudinal Study - Jenert, Tobias; Brahm, Taiga
The aim of this qualitative study is first to investigate the attitude development of students in their initial year at university. College effectiveness research has shown that attitudes towards studying as well as to one's university are key factors influencing student engagement. Up to now, little is known about the processes through which such attitudes develop. Based on the theory of planned behaviour (Ajzen & Fishbein, 1980), the study addresses this research gap in three parts: a) development paths of students' attitudes towards studying and the university; b) the normative behaviour of the fellow students as well as significant persons, c) university-related experiences during the first year influencing students' attitude development. To answer these research questions, a series of five interviews was conducted throughout the first year with a total of 13 first-year students at the University of St. Gallen/Switzerland. Data analysis was performed referring to the procedures suggested by Neale (2012) for qualitative longitudinal data. To master the challenge of displaying developments over time, graphical analysis was used to construct a case history (cf. Henderson, Holland et al., 2012) for each individual. Regarding the students' developments over time, the analysis shows the participants' attitudes towards the university became more differentiated over time. A second major result concerns frictions between students' own attitudes and what they perceive to be the dominant normative behaviour. It became obvious that this developmental process is influenced by concrete incidents students experience during the first year and thus, can be shaped by structural changes.
Keywords: student attitudes; qualitative research; longitudinal study; student motivation

A latent growth curve analysis of Business students' intrinsic and extrinsic motivation - Brahm, Taiga; Jenert, Tobias
The proposed paper aims to investigate the longitudinal development of students' motivation over the first year of their studies at a business school by using latent growth curve modeling. The study tackles the following core research questions: How do first-year university students' intrinsic and extrinsic vary over time? Which (motivational) factors are related to students' motivational development? Although motivational dispositions have been analyzed extensively in previous studies, their longitudinal development has hitherto not been examined in the higher education context. This longitudinal study is conducted at the University of St. Gallen in Switzerland. The current sample includes 280 first-year students who have been surveyed three times and who are representative of the first-year student population. Descriptive results show that prior to their studies, students were motivated most by intrinsic factors, however, extrinsic motivation was also quite high. Employing latent growth curve modeling, it could be shown that both intrinsic and extrinsic motivation decline significantly over the course of the first year (8 months). The study contributes to motivation theory by providing further insights into the development of academic motivation over time. Latent growth curve modeling as a method can be well used for longitudinal data analysis, thus, excluding measurement error from longitudinal data. Furthermore, the study supports educational developers by determining factors influencing students' motivational development.
Keywords: motivation; intrinsic motivation; extrinsic motivation; latent growth curve modeling; longitudinal data analysis; ASEQ; higher education; studying

Exploring Intermediate Vocational Education and Training for 16-19 Year-olds in Germany and England - Higham, J. J. S.; Kremer, H.-Hugo; Yeomans, D. (The Architecture of Innovative Apprenticeship)

A story about a word: does narrative presentation promote learning of a spatial preposition in German two-year-olds? - Nachtigäller, Kerstin; Rohlfing, Katharina; McGregor, Karla K. (Journal of Child Language)
We trained forty German-speaking children aged 1;8–2;0 in their comprehension of UNTER [UNDER]. The target word was presented within semantically organized input in the form of a ‘narrative’ to the experimental group and within ‘unconnected speech’ to the control group. We tested children’s learning by asking them to perform an UNDER-relation before, immediately after, and again one day after the training using familiarized and unfamiliarized materials. Compared to controls, the experimental group learned better and retained more. Children with advanced expressive lexicons in particular were aided in generalizing to unfamiliarized materials by the narrative presentation. This study extends our understanding of how narrations scaﬀold young children’s enrichment of nascent word knowledge.

Biases in Management Forecasts of Venture-Backed Start-Ups: Evidence from Internal Due Diligence Documents of VC Investors - Sievers, Sönke; Mokwa, Christopher Frederik
This study provides evidence of significant biases in multi-year management forecasts by analyzing a proprietary dataset on venture-backed start-ups in Germany. We find that revenues and expenses are highly overestimated in each of the investigated one- to five-year-ahead planning periods. Furthermore, entrepreneurs underestimate one-year-ahead profit forecasts but clearly overestimate their profit forecasts for all longer-term forecast horizons. Additional analyses reveal that teams with prior management experience issue even more overestimated forecasts and misrepresent their forward-looking information. In contrast, greater asset verifiability and corporate lead investors are associated with lower levels of forecast errors. All key results hold if bias is either measured by traditionally comparing forecasts to ex-post realizations or by using a cross-sectional projection approach based on historical accounting data developed by prior research.
Keywords: Management forecasts; Forecasting biases; Venture-backed start-ups; Projection methods

The Relevance of Biases in Management Forecasts for Failure Prediction in Venture Capital Investments - Sievers, Sönke; Mokwa, Christopher Frederik
This study shows how venture capital investors can identify potential biases in multi-year management forecasts before an investment decision and derive significantly more accurate failure predictions. By advancing a cross-sectional projection method developed by prior research and using firm-specific information in financial statements and business plans, we derive benchmarks for management revenue forecasts. With these benchmarks, we estimate forecast errors as an a priori measure of biased expectations. Using this measure for our proprietary dataset on venture-backed start-ups in Germany, we find evidence of substantial upward forecast biases. We uncover that firms with large forecast errors fail significantly more often than do less biased entrepreneurs in years following the investment. Overall, our results highlight the implications of excessive optimism and overconfidence in entrepreneurial environments and emphasize the relevance of accounting information and business plans for venture capital investment decisions.
Keywords: Management forecast biases; cross-sectional projection models; venture-backed start-ups; failure prediction; overoptimism; overconfidence

Self-Organizing Particle Systems - Drees, Maximilian; Hüllmann (married name: Eikel), Martina; Koutsopoulos, Andreas; Scheideler, Christian (Proceedings of the 26th IEEE International Parallel and Distributed Processing Symposium (IPDPS))
Nanoparticles are getting more and more in the focus of the scientic community since the potential for the development of very small particles interacting with each other and completing medical and other tasks is getting bigger year by year. In this work we introduce a distributed local algorithm for arranging a set of nanoparticles on the discrete plane into specic geometric shapes, for instance a rectangle. The concept of a particle we use can be seen as a simple mobile robot with the following restrictions: it can only view the state of robots it is physically connected to, is anonymous, has only a constant size memory, can only move by using other particles as an anchor point on which it pulls itself alongside, and it operates in Look-Compute-Move cycles. The main result of this work is the presentation of a random distributed local algorithm which transforms any given connected set of particles into a particular geometric shape. As an example we provide a version of this algorithm for forming a rectangle with an arbitrary predened aspect ratio. To the best of our knowledge this is the rst work that considers arrangement problems for these types of robots.

The Relevance of Biases in Management Forecasts for Failure Prediction in Venture Capital Investments - Mokwa, Christopher Frederik; Sievers, Sönke (SSRN Electronic Journal)
This study shows how venture capital investors can identify potential biases in multi-year management forecasts before an investment decision and derive significantly more accurate failure predictions. By advancing a cross-sectional projection method developed by prior research and using firm-specific information in financial statements and business plans, we derive benchmarks for management revenue forecasts. With these benchmarks, we estimate forecast errors as an a priori measure of biased expectations. Using this measure for our proprietary dataset on venture-backed start-ups in Germany, we find evidence of substantial upward forecast biases. We uncover that firms with large forecast errors fail significantly more often than do less biased entrepreneurs in years following the investment. Overall, our results highlight the implications of excessive optimism and overconfidence in entrepreneurial environments and emphasize the relevance of accounting information and business plans for venture capital investment decisions.
Keywords: Management forecast biases; cross-sectional projection models; venture-backed start-ups; failure prediction; overoptimism; overconfidence

Biases in Management Forecasts of Venture-Backed Start-Ups: Evidence from Internal Due Diligence Documents of VC Investors - Mokwa, Christopher; Sievers, Sönke (SSRN Electronic Journal)
This study provides evidence of significant biases in multi-year management forecasts by analyzing a proprietary dataset on venture-backed start-ups in Germany. We find that revenues and expenses are highly overestimated in each of the investigated one- to five-year-ahead planning periods. Furthermore, entrepreneurs underestimate one-year-ahead profit forecasts but clearly overestimate their profit forecasts for all longer-term forecast horizons. Additional analyses reveal that teams with prior management experience issue even more overestimated forecasts and misrepresent their forward-looking information. In contrast, greater asset verifiability and corporate lead investors are associated with lower levels of forecast errors. All key results hold if bias is either measured by traditionally comparing forecasts to ex-post realizations or by using a cross-sectional projection approach based on historical accounting data developed by prior research.
Keywords: Management forecasts; Forecasting biases; Venture-backed start-ups; Projection methods

Regional and socio-economic differences in food, nutrient and supplement intake in school-age children in Germany: results from the GINIplus and the LISAplus studies - Sausenthaler, Stefanie; Standl, Marie; Buyken, Anette; Rzehak, Peter; Koletzko, Sibylle; Bauer, Carl Peter; Schaaf, Beate; von Berg, Andrea; Berdel, Dietrich; Borte, Michael; Herbarth, Olf; Lehmann, Irina; et al. (Public Health Nutrition)
Abstract Objective To describe regional differences between eastern and western Germany with regard to food, nutrient and supplement intake in 9–12-year-old children, and analyse its association with parental education and equivalent income. Design Data were obtained from the 10-year follow-up of the two prospective birth cohort studies – GINIplus and LISAplus. Data on food consumption and supplement intake were collected using an FFQ, which had been designed for the specific study population. Information on parental educational level and equivalent income was derived from questionnaires. Logistic regression modelling was used to analyse the effect of parental education, equivalent income and region on food intake, after adjusting for potential confounders. Setting Germany. Subjects A total of 3435 children aged 9–12 years. Results Substantial regional differences in food intake were observed between eastern and western Germany. Intakes of bread, butter, eggs, pasta, vegetables/salad and fruit showed a significant direct relationship with the level of parental education after adjusting for potential confounders, whereas intakes of margarine, meat products, pizza, desserts and soft drinks were inversely associated with parental education. Equivalent income had a weaker influence on the child's food intake. Conclusions Nutritional education programmes for school-age children should therefore account for regional differences and parental education.

Buy, Sell, or Hold? Information Extraction from Stock Analyst Reports - Lee, Yeong Su; Geierhos, Michaela (Modeling and Using Context: 7th International and Interdisciplinary Conference, CONTEXT 2011, Karlsruhe, Germany, September 26-30, 2011, Proceedings)
This paper presents a novel linguistic information extraction approach exploiting analysts’ stock ratings for statistical decision making. Over a period of one year, we gathered German stock analyst reports in order to determine market trends. Our goal is to provide business statistics over time to illustrate market trends for a user-selected company. We therefore recognize named entities within the very short stock analyst reports such as organization names (e.g. BASF, BMW, Ericsson), analyst houses (e.g. Gartner, Citigroup, Goldman Sachs), ratings (e.g. buy, sell, hold, underperform, recommended list) and price estimations by using lexicalized finite-state graphs, so-called local grammars. Then, company names and their acronyms respectively have to be cross-checked against data the analysts provide. Finally, all extracted values are compared and presented into charts with different views depending on the evaluation criteria (e.g. by time line). Thanks to this approach it will be easier and even more comfortable in the future to pay attention to analysts’ buy/sell signals without reading all their reports.

Sound & Image. An experimental study on the influence of acoustical parameters on the perception of a product’s image in TV-commercials - Flath, Beate (Audio Branding Year Book 2010)

Trends in dietary carbohydrate quality during puberty from 1988 to 2007: a cause for concern? - Cheng, Guo; Libuda, Lars; Karaolis-Danckert, Nadina; Alexy, Ute; Bolzenius, Katja; Remer, Thomas; Buyken, Anette (British Journal of Nutrition)
The extent to which the quality of dietary carbohydrates (CHO) changes throughout puberty is not known. We analysed trends in the quantity and quality of CHO intake among German adolescents by separately examining trends during puberty (pubertal trends) and trends in CHO intake from 1988 to 2007 (secular trends). Linear mixed-effects regression analyses were performed in 216 participants of the Dortmund Nutritional and Anthropometric Longitudinally Designed Study who had provided weighed 3 d dietary records at the onset of the pubertal growth spurt (defined by age at take-off) and over the subsequent 4 years. Over the course of puberty, CHO quality changed little: added sugar intake from beverages increased in girls (0·25 ( se 0·12) % energy (% E)/year, P = 0·04) and added sugar intake from sweets decreased in both sexes (boys: − 0·22 ( se 0·11) % E/year, P = 0·049; girls: − 0·20 ( se 0·10) % E/year, P = 0·04). For both sexes, significant upward secular trends were observed for CHO (% E), glycaemic load (g/MJ) and added sugar intakes from sources other than sweets and soft drinks (% E), while absolute fibre intake (g/d) decreased ( P ≤ 0·04). Concomitant increases in total added sugar intake (% E) and decreases in fibre and whole-grain densities (g/MJ) ( P = 0·001–0·02) were confined to boys only. The quality of dietary CHO consumed by healthy German adolescents shows notable secular declines, but does not change markedly during puberty. Public health initiatives should be tailored to improve the overall quality of CHO nutrition.

Type 2 diabetes mellitus and risk of coronary heart disease: results of the 10-year follow-up of the PROCAM study - Buyken, Anette; von Eckardstein, Arnold; Schulte, Helmut; Cullen, Paul; Assmann, Gerd (European Journal of Cardiovascular Prevention & Rehabilitation)

Armed for the spam battle - a technological and organizational infrastructure framework - Schryen, Guido (40th Annual Hawaii International Conference on System Sciences)
Spamming remains a form of Internet abuse, which burdens the Internet infrastructure, is generally regarded as an annoyance, and is said to cause economic harm to the tune of about several billion US\$ per year. Many technological, organizational, and legislative anti-spam measures have already been proposed and implemented, but have not led to any substantial decrease in the number of spam e-mails. We propose here a new infrastructure framework that combines several anti-spam measures in a framework that features both a technological and an organizational facet. The key element of our infrastructure is a new organizational unit that reliably and transparently limits he number of e-mails that can be sent per day and per account. This paper first gives an overview of the framework, then it provides technological and organizational details of the infrastructure, the deployment of which depends to a large degree on its acceptance and propagation by the ICANN, the ISOC, and by large e-mail service providers. Finally, the paper discusses the limitations and drawbacks of the proposed framework.

Well-being and the child-parent relationship at the transition from university to work life - Buhl, Heike M. (Journal of Adolescent Research)
This longitudinal study addresses the impact of the transition from university to work life on emerging adults' well-being and their relationship with their parents. A sample of 102 German students attending their last year at the university (M = 25.44 years, SD = 2.61) completed a questionnaire. Among others, scales from the Network of Relationships Inventory and symptom checklists were administered. Four years later, 51 employed participants of the initial sample were contacted again. During the transition from university to work life, well-being and the relationship with their parents improved. Following a typological approach, two groups of emerging adults were revealed by means of cluster analyses. Well-being in one group increased, whereas well-being in the second group decreased. Group membership was predicted by sex, personality, and the child–parent relationship in university times.

One Year operation of Offshore Metmast Amrumbank West - Bendfeld, Jörg; Splett, Michael; Voss, Jürgen; Higgen, Anne; Krieger, Jens

Optical properties of semiconductor photonic-crystal structures: spatially-inhomogeneous excitonic resonances and optical gain - Meier, Torsten; Reichelt, Matthias; Pasenow, B.; Stroucken, T.; Koch, S.W. (2005 annual conference of the German Physical Society (DPG) during the World year of physics)

Teaching Object-Oriented Concepts with Eclipse - Meyer, Matthias; Wendehals, Lothar (Proc. of the Eclipse Technology eXchange Workshop (ETX), Satellite Event of the 19th Conference on Object-Oriented Programming, Systems, Languages, and Applications (OOPSLA), Vancouver, Canada)
Object-oriented software development is a subject area difficult to teach, espcially to beginners. They face a lot of abstraction and (from a beginners point of view) isolated topics, such as the syntax and semantics of a programming language, the functionality of a software development environment and basic object-oriented concepts. Although many professionals in education believe in the ``object first'' approach as the best method of introducing object-oriented concepts, there is no common agreement on how to start such courses. Current study programs often begin by teaching a programming language, instead of focusing on the basics of object-oriented concepts. In the last years a learning environment was developed based on a visual programming language to abstract away from details. It assists teaching step-by-step object-oriented concepts and the syntax and semantics of a programming language in secondary schools and first year university courses. Our goal is to port this learning environment to the widely used IDE Eclipse.

Storage Management as Means to cope with Exponential Information Growth - Scheideler, Christian; Salzwedel, Kay; Meyer auf der Heide, Friedhelm; Brinkmann, André; Vodisek, Mario; Rückert, Ulrich (Proceedings of SSGRR 2003)
The advances in Internet technology have led to tremendous improvements in business, education, and science and have changed the way we think, live, and communicate. Information exchange has become ubiquitous by the possibilities offered through modern technologies. We are able to offer information 24 hours a day through our web sites and can leave messages every time and from anywhere in the world. This change in communication has led to new challenges. Enterprises have to deal with an information amount that doubles every year. The technological foundation to cope with this information explosion is given by Storage Area Networks (SANs), which are able to connect a great number of storage systems over a fast interconnection network. However, to be able to use the benefits of a SAN, an easy-to-use and efficient management support has to be given to the storage administrator. In this paper, we will suggest new storage management concepts and we will introduce a new management environment that is able to significantly reduce management costs and increases the performance and resource utilization of the given SAN infrastructure.

Players, Playthings and Patterns: Three Stages of Heteronomy in Beckett's Mature Drama - Tönnies, Merle (Samuel Beckett Today / Aujourd'hui: Endlessness in the Year 2000 / Fin sans fin en l'an 2000)